2020
DOI: 10.1002/aqc.3283
|View full text |Cite
|
Sign up to set email alerts
|

The influence of seagrass donor source on small‐scale transplant resilience

Abstract: 1. Concern for conservation of seagrass habitat has prompted international transplantation-style restoration efforts. A recent review of these restoration efforts has highlighted the low success associated with small-scale restorations, yet scaling up transplantation effort may be too costly for underfunded regions. Small-scale transplant survival can be enhanced with alleviation of two underlying issues: restoration site selection and donor site selection. 2. To investigate appropriate donor source selection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Third, a global analysis has shown that large-scale restoration trials are on average more successful than small-scale trials (van Katwijk et al 2016 ). Finally, in multisite, multiyear restoration programs, it is often observed that only a few trials within the program expand vigorously, whereas the remaining trials fail (Suykerbuyk et al 2016 , Paulo et al 2019 , McDonald et al 2020 ). These failures can often be explained in hindsight (McDonald et al 2020 ) or, at least, alluded to (Suykerbuyk et al 2016 , Paulo et al 2019 ), but they cannot be predicted, suggesting the operation of chance dynamics in the recovery process.…”
Section: Why We Cannot Rely On Natural Recovery Alonementioning
confidence: 99%
“…Third, a global analysis has shown that large-scale restoration trials are on average more successful than small-scale trials (van Katwijk et al 2016 ). Finally, in multisite, multiyear restoration programs, it is often observed that only a few trials within the program expand vigorously, whereas the remaining trials fail (Suykerbuyk et al 2016 , Paulo et al 2019 , McDonald et al 2020 ). These failures can often be explained in hindsight (McDonald et al 2020 ) or, at least, alluded to (Suykerbuyk et al 2016 , Paulo et al 2019 ), but they cannot be predicted, suggesting the operation of chance dynamics in the recovery process.…”
Section: Why We Cannot Rely On Natural Recovery Alonementioning
confidence: 99%
“…Additionally, when genotypes or species have different and asynchronous responses to disturbances and stress, this can lead to increased stability and is termed the ‘insurance hypothesis’ (Yachi & Loreau, 1999). Seagrass rhizomes store non–structural carbohydrates that can be mobilized to facilitate re‐growth following disturbances or stress (Sanmartí et al, 2014), and variation in rhizome carbohydrate storage as well as variation in plant growth rates among seagrass species and genotypes can drive delayed and asynchronous responses to disturbances (Barry et al, 2018; Dawes & Lawrence, 1980; Evans et al, 2018; Hughes et al, 2009; Maxwell et al, 2014; McDonald et al, 2020; Ralph et al, 2007; Reynolds et al, 2016; Touchette & Burkholder, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The fourth method can damage the donor meadow and, in addition, generate changes in local sediment dynamics with erosive impacts, which may impair or delay the recolonization (Maxwell et al 2017; Githaiga et al 2019). Plants can be extracted from a donor meadow with or without sediments, but the introduction of transplants with the original sediments preserves the rooting environment and provides better anchorage, resulting in successful transplant establishment (Paling et al 2001; Hall et al 2006; McDonald et al 2020). Paulo et al (2019) comment that the failure rate of using sediment‐free methods has been high (e.g., 100% failure for Zostera marina , Zostera noltei , and Cymodocea nodosa in Portugal) and recommend using seagrass harvesting methods with their natural sediment.…”
Section: Introductionmentioning
confidence: 99%
“…Paulo et al (2019) comment that the failure rate of using sediment‐free methods has been high (e.g., 100% failure for Zostera marina , Zostera noltei , and Cymodocea nodosa in Portugal) and recommend using seagrass harvesting methods with their natural sediment. Sods and cores/plugs are the most common and effective extraction methods with sediments, but small‐sized cores are preferred if the damage to the donor meadow should be minimized (Verduin et al 2012; Paulo et al 2019; McDonald et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation